(untitled) (ModaPalavra e-periódico, 2024)
This article aims to understand the space for diversity in the fashion content of six important fashion magazines in the country. The study evaluates the content of posts on the Instagram social network of Vogue Brasil, Elle Brasil, Harper’s Bazaar, Glamour Brasil, Marie Claire Brasil and L’Officiel Brasil. The time frame is three months and accounts for 3,083 pieces of content - from August 1 to October 31, 2022. This is a descriptive and exploratory study which aimed to identify the most common subject in the posts, which focus, national or international, was given to the coverage on the social network, assess the degree of factuality in the coverage and, finally, identify the space that this content gave to diversity. The result shows that the editorial proposals that magazines favor on Instagram have devoted little space to difference. Although there are some initiatives that seek to bring greater visibility and representativeness to varied groups, most of the publications on the social networks of these magazines perpetuate idealized standard models of beauty, which exclude people of different ethnic origins, body sizes and other physical characteristics. This has led to a limited and stereotyped in fashion magazines, which perpetuates a racist and discriminatory view of society.